ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN DAYA SAING USAHA INDUSTRI MEBEL DI KOTA TIMIKA - Tiara Lestari; Nurul Hidayat Lestaluhu; Rulan L. Manduapessy (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the factors that determine the competitiveness of the furniture industry in Timika City. This study uses an associative method using the Confirmatory Factor Analysis analysis tool. The data used in this study are primary data sourced from furniture entrepreneurs in Timika City. The results of the study indicate that the product quality factor is able to explain competitiveness by 42.443%, the promotion factor is able to explain competitiveness by 8.651%, the location factor is able to explain competitiveness by 9.962% and the price factor is able to explain competitiveness by 10.898%. Where the product quality, promotion, location and price factors are able to explain competitiveness by 71.954%.